INNOVATIVE PEDAGOGICAL APPROACHES TO DEVELOPING MEDIA COMPETENCE OF FUTURE TEACHERS IN THE DIGITAL AGE (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article analyzes the processes of corporate strategy formation in building materials manufacturing enterprises based on scientific and practical approaches. The study examines the interrelationship of micromarkets, production strategy, innovative technologies, and sustainability principles. International experiences, including strategies of large companies, are compared with the possibilities of application in national conditions. The results show that a comprehensive strategy based on market signals, production decisions, and environmental requirements increases the long-term competitiveness and economic efficiency of enterprises.